PEPS-KL: An Ecoliteracy Intervention for Plastic Waste Management Education - Massinai, Sitti Muthia Maghfirah; Jamal, Noor Dyah Utami; Almira, Nurul Insani; Massinai, Muhammad Altin (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to enhance the ecoliteracy of high school students in plastic waste management through the Program Edukasi Pengelolaan Sampah Plastik untuk Keberlanjutan Lingkungan (PEPS-KL) at SMAN 1 Takalar, Takalar Regency, South Sulawesi. The program was developed using the Community-Based Participatory Research (CBPR) method, incorporating the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with an experiential learning approach. Participants comprised 35 tenth-grade students who participated in an intensive 6-hour learning program. Evaluation was conducted using a one-group pretest-posttest design with quantitative analysis through the Wilcoxon Signed Ranks Test and qualitative analysis through content analysis of participants' reflections. The program successfully improved participants' knowledge significantly (Z = -5.067, p < 0.001) with an average score increase of 55.01% from pretest (M = 6.69) to posttest (M = 10.37). A total of 94.3% of participants experienced improved understanding of ecoliteracy. Qualitative evaluation revealed participants' holistic transformation encompassing critical awareness of microplastic impacts, intrinsic motivation for change, positive emotional responses, construction of new knowledge, and commitment to becoming agents of environmental change. PEPS-KL proved effective in facilitating holistic learning that encompasses the cognitive, affective, and conative domains, which are essential to developing effective and sustainable environmental education strategies at the high school level.